2020
DOI: 10.3390/coatings10030259
|View full text |Cite
|
Sign up to set email alerts
|

Films of Chitosan and Aloe vera for Maintaining the Viability and Antifungal Activity of Lactobacillus paracasei TEP6

Abstract: The present study aimed to evaluate the effect of Aloe vera addition on the viability and antifungal activity of TEP6 (Lactobacillus paracasei) bacteria immobilized on chitosan films for 28 days. Different chitosan and A. vera proportions and carbon sources at several pH values were tested as formulations for supporting the microorganism. Bacterial viability was maintained in freshly made films, with values of 10.4, 10.8 and 10.9 log CFU·g−1 for the formulations containing 70% (T11), 100% (T8) and 100% (T16) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…They reported that the film containing cinnamon oil showed maximum antimicrobial activity among the three oils against Aspergillus oryzae and Penicillium digitatum fungi than gram-positive (S. aureus) and gram-negative (E. coli) bacteria. Barragán-Menéndez et al 45 evaluated the effect of aloevera incorporated with chitosan to study the feasibility and antifungal activity of TEP6 (Lactobacillus paracasei) bacteria on chitosan films. They reported that maximum viability of the film can be seen with higher aloevera concentration and at pH 4.5.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…They reported that the film containing cinnamon oil showed maximum antimicrobial activity among the three oils against Aspergillus oryzae and Penicillium digitatum fungi than gram-positive (S. aureus) and gram-negative (E. coli) bacteria. Barragán-Menéndez et al 45 evaluated the effect of aloevera incorporated with chitosan to study the feasibility and antifungal activity of TEP6 (Lactobacillus paracasei) bacteria on chitosan films. They reported that maximum viability of the film can be seen with higher aloevera concentration and at pH 4.5.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…23 Aloe vera was another plant used in the preparation of chitosan films, in this case, to maintain the viability and antifungal activity of Lactobacillus paracasei TEP6, a microorganism integrating into the material; this biomaterial has been used as a coating for vegetables to prevent the growth of the Colletotrichum gloeosporioides fungi. 24 Microbial biosynthesis uses different microorganisms to produce a large variety of industrial products for human interest. 25 Saccharomyces cerevisiae (S. cerevisiae) is a nonpathogenic yeast and the best-studied eukaryote.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, plant extracts have been used to modify the physicochemical properties of materials, enhancing their ability to integrate cells by increasing cell adhesion and cell viability within the material. , Calendula officinalis (C. officinalis) is an important medicinal plant with potential biological properties; its hydroalcoholic extract has been used to elaborate films with improved adhesion and viability for human fibroblasts as well as other eukaryotic cells such as Candida albicans …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations